2020
DOI: 10.1002/dvdy.149
|View full text |Cite
|
Sign up to set email alerts
|

Defective coronary vessel organization and reduction of VEGF‐A in mouse embryonic hearts with gestational mild hypoxia

Abstract: Background: Vasculature is formed by responding to homeostatic tissue demands including in developing hearts. Hypoxia generally stimulates vascular formation in which vascular endothelial growth factor A (VEGF-A) plays a critical role. Gestational hypoxia increases the risk of low intrauterine growth and low birth weight, both of which are known to increase the risk of the fetus developing cardiovascular defects. In fact, continuous gestational mild hypoxia (14% O 2 ) from the mid-embryonic stage causes cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Annexin A1 (AnxA1) directly led cardiac macrophages to polarize to angiogenic and repair phenotypes, and stimulated cardiac macrophages to release large amounts of VEGF-A, thus inducing angiogenesis and cardiac repair (20). By contrast, one study revealed that mild hypoxia (14% O 2 ) did not induce coronary angiogenesis or VEGF-A expression in hearts of developing mice (21).…”
Section: Mechanisms Regulating the Level Of Vegf-a Upregulation Mechanism Of Vegf-amentioning
confidence: 99%
“…Annexin A1 (AnxA1) directly led cardiac macrophages to polarize to angiogenic and repair phenotypes, and stimulated cardiac macrophages to release large amounts of VEGF-A, thus inducing angiogenesis and cardiac repair (20). By contrast, one study revealed that mild hypoxia (14% O 2 ) did not induce coronary angiogenesis or VEGF-A expression in hearts of developing mice (21).…”
Section: Mechanisms Regulating the Level Of Vegf-a Upregulation Mechanism Of Vegf-amentioning
confidence: 99%